Panggilan Gereja dalam Realitas Ketidakadilan di Indonesia - Utomo, Kurniawan Madyo (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2023)
The issue of injustice (corruption, buying and selling legal cases, welfare for the poor, etc.) that causes people to suffer still frequently occurs in Indonesia. In a life of faith, faith must be revealed through actions that bring justice and love to those who are suffering. The purpose of this research is to answer questions about how Christians live out their faith and how the Church manifests the presence of God in the reality of injustice. The method used in this research is qualitative, employing literature studies. Church documents and the thoughts of theologians discussing the Church's calling in the midst of the reality of injustice are examined using critical discourse analysis. The results of this research show that in the midst of the reality of injustice, the Church must present itself as a sacrament of God’s presence that desires human beings to live. It must restore the dignity of both the victims and perpetrators of injustice. It also needs to engage in dialogue and collaboration with people of other religions to address the issue of injustice.